HPV genotypes in invasive cervical cancer: prevalence, risk attribution, and optimized vaccine strategies in western China - Yuling Kou; Yuling Kou; Xiao Tang; Xiao Tang; Dongni Liang; Dongni Liang; Chuan Xie; Chuan Xie; Jing Zeng; Jing Zeng; Meng Chen; Meng Chen; et al. (Frontiers in Public Health)
BackgroundUnderstanding the HPV genotype distribution in invasive cervical cancer (ICC) is essential for vaccine optimization. This study presents a comprehensive analysis of HPV genotypes in ICC tissues from patients in western China, with the aim of informing regional vaccine policy and prevention strategies.MethodsDNA was extracted from 1,908 paraffin-embedded ICC samples, and 23 HPV genotypes were detected via PCR and reverse dot hybridization gene chip assays. The genotypic distribution of HPV infections was analyzed, the attribution of each HPV genotype found in multiple infection cases was calculated using the fractional contribution approximation. Furthermore, the cumulative attribution rates of HPV genotypes included in each vaccine combination were totaled to estimate the potential vaccination coverage of ICC across various histologic types and age groups.ResultsThe overall prevalence of HPV infection was 94.9% (95% CI 93.8–95.8) among 1,908 women with ICC. HPV genotypes 16 and 18 were detected in 1645 of 1810 HPV-positive patients (90.9, 95% CI 89.5–92.1) of ICC. HPV16, 18, 33, 52, and 58 were detected in 1,749 patients (96.6, 95% CI 95.7–97.4), the five most common genotypes in different age groups. HPV genotypes contained in the 9-valent vaccine were detected in 1776 patients (98.1, 95% CI 97.4–98.7). By weighted imputation analysis, the cumulative attribution rates of the bivalent vaccine was 83.4%, and that of the nine-valent vaccine was 89.8%. Optimization group A included the five genotypes with the highest prevalence, HPV16, 18, 33, 52, and 58, with a cumulative attribution rates of 88.5%, and optimization group B included the nine most common HPV genotypes, HPV16, 18, 31, 33, 35, 45, 52, 58, and 59, with a cumulative attribution rates of 90.5%.ConclusionOur comprehensive postsurgical analysis of HPV in ICC patients in western China revealed that the incorporation of the bivalent vaccine into the national program is cost-effective, with group A optimization closely matching the vaccination coverage of the 9-valent vaccine, which can be used to guide future prevention strategies.